Perfil epidemiológico dos pacientes notificados com AIDS no município de Sete Lagoas, Minas Gerais - Souza, Eliana Soares de (2007)
In order to understand the epidemiological characteristics of AIDS notifications in the municipality of Sete Lagoas, Minas Gerais, data from 138 resident patients and those who were notified from 1986 to 2004 were analyzed. For this purpose, data from the Notification / Investigation form were used ( patients aged 13 or over) of the Notifiable Diseases Information System (SINAN). The variables evaluated in this study were: sex, age, education, sexual relations, sexual relations with individuals known to be HIV / AIDS, information about sexual partner, date of diagnosis, date of notification, current situation and date of death. In this way, the frequencies of the studied variables were distributed using the Epinfo 6.0 program. It was found that the concentration of cases was in the age group of 33 to 37 years, that is, young adults. Regarding the gender variable, what was observed was a tendency towards feminization. Regarding the level of education, what was found was a concentration of 30.4% of individuals with 4 to 7 years of study, which characterizes low education. Regarding the category of sexual transmission, 32% of men who have sex with men, 29% with women and 15.2% with both were registered. Of the total of 29 cases that answered yes to sexual relations with individuals known to be HIV / AIDS, 58.6% were women. Regarding sexual partner, four patients confirmed bisexual partner and 14 reported partner (a) user of intravenous illicit drugs. Among the opportunistic diseases, Pneumocystis jerovesi pneumonia, cachexia, asthenia, candidiasis, extrapulmonary cryptococcosis and cytomegalovirus were highlighted. The average survival was 13 months, with a concentration of cases (63%) with an average of up to 6 months of survival. It is concluded that the AIDS cases reported in Sete Lagoas-MG are of young adult individuals, with low education, most of them females, partners of individuals with HIV / AIDS and with an average survival of 13 months.